THE COMPARATIVE ANALYSIS OF STUDENTS’ LEARNING STYLES ON THEIR ACHIEVEMENT IN READING SKILLS - Eka Dewi Fithrotunnisa; Eneng Liah Khoiriyah; Dede Imtihanudin (Cakrawala Pedagogik, 2022)
The aim of the study is to know the difference between students learning styles. The study was held in the second grade of Madrasah Tsanawiyah Attaubah Batu Bantar Pandeglang. The research method of this study is a causal-comparative (ex post facto) using a purposive sampling technique. The 30 students were involved in the research. They were classified into three different learning styles through a test. The Percentage and bifilar linear regression analysis were used to analyze the collected data. The majority of students had a visual learning style according to the data analysis. The other two are kinesthetic and auditory learning style. 54,9% of students' English achievement is influenced by learning styles and 45,1% is influenced by other factors. According to the data, it can be concluded that the visual learning style is the best way to get a better comprehension of reading skills.